Effect Of Scrubber Operation On Airflow And Methane Patterns At The Mining Face - J. E. Chilton (The National Institute for Occupational Safety and Health (NIOSH))
The National Institute for Occupational Safety and Health (NIOSH) has conducted research to determine the influence of mining machine-mounted scrubbers on airflows and methane concentrations at the face when blowing ventilation systems are used. Tests were conducted in a full-scale ventilation gallery with a model mining machine that simulated airflow created by a dust scrubber. During the tests, ultrasonic anemometers were used to measure airflow speed and direction at several locations near the face. For the same test conditions, methane was released from the face and gas concentrations were measured at 21 locations above the machine using fixed point methanometers. Changes in airflow speed and direction are correlated with scrubber airflow and the measured methane distribution above the mining machine. The research results showed that operation of machine-mounted scrubbers improved face ventilation when blowing ventilation is used by increasing both the intake flow and the quantity of air reaching the face.